2024
DOI: 10.51582/interconf.19-20.01.2024.060
|View full text |Cite
|
Sign up to set email alerts
|

Technological line for production of activated powders by hydro-vacuum dispersion of liquid metals

David Sakhvadze,
Gigo Jandieri,
Giorgi Sakhvadze
et al.

Abstract: This article is a short scientific communication devoted to substantiation of expediency of industrial implementation and further development of our innovative unified development of hydro-vacuum dispersion of metallic melts. Here the basic principles of the dispersing line functioning are given and its advantages over traditional technologies are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Perspectives for development Based on the above analysis, we concluded that there is a new possibility of improving the technology of direct alloying of steel and alloys, which is associated with the prospect of using as an active reducing agent obtained specifically for this purpose hydrogenated aluminum powder AlH 3 (H 1-5%). We were the first to obtain such a powder as a by-product of hydro-vacuum dispersion of liquid aluminum No 193 superheated at 150 o C. The observed effect was achieved by operating our hydro-vacuum dispersion unit [25] in the mode of generating a high-frequency cavitation-wave field [26] and initiating sonochemical hydrogenation reactions. According to the study of [27], the general sonochemical hydrogenation reaction of metal powder particles can be written as follows:…”
Section: Current State Of the Problemmentioning
confidence: 99%
“…Perspectives for development Based on the above analysis, we concluded that there is a new possibility of improving the technology of direct alloying of steel and alloys, which is associated with the prospect of using as an active reducing agent obtained specifically for this purpose hydrogenated aluminum powder AlH 3 (H 1-5%). We were the first to obtain such a powder as a by-product of hydro-vacuum dispersion of liquid aluminum No 193 superheated at 150 o C. The observed effect was achieved by operating our hydro-vacuum dispersion unit [25] in the mode of generating a high-frequency cavitation-wave field [26] and initiating sonochemical hydrogenation reactions. According to the study of [27], the general sonochemical hydrogenation reaction of metal powder particles can be written as follows:…”
Section: Current State Of the Problemmentioning
confidence: 99%